Evaluating the effects of transverse bar on vehicle speed at an arterial road in Kuala Lumpur - Mohd, Nur Shuhadah; Kadar Hamsa, Abdul Azeez (Eastern Asia Society for Transportation Studies, 2017)
Road safety is a major concern for road users. Vehicles traveling at speeds higher than the speed limit are one of the main reasons for the increased number of accidents along arterial roads in Malaysia. Transverse bars are considered as an effective measure in addressing the increased speed of traffic along arterial roads. This paper investigates the effects of transverse bars on the speed of the vehicles at a road segment along an arterial road in Kuala Lumpur. Two sets of transverse bars at an arterial road in Kuala Lumpur were selected. The design profiles and spot speed of the vehicles at the two selected transverse bars were measured. The speed of the vehicles before, on and after the transverse bars was analysed. The findings show despite the speed of the vehicles having decreased when approaching towards transverse bars, the speed still remains higher than the permissible speed limit.